The epidemiology of laryngeal cancer in Brazil - Wünsch Filho, Victor (São Paulo Medical Journal, 2004)
The city of São Paulo exhibits one of the highest incidences of laryngeal cancer in world and Brazil presents remarkable occurrence, compared with other Latin American countries. Around 8,000 new cases and 3,000 deaths by laryngeal cancer occur annually in the Brazilian population. In the city of São Paulo, incidence rates for laryngeal cancer among males have been decreasing since the late 1980s while, among females, the rates have shown a stable trend. This phenomenon is probably the expression of changes in gender behavior related to tobacco smoking. Several risk factors are involved in the genesis of laryngeal cancer. The most important are tobacco smoking and alcohol intake, but occupational hazards have also been associated with the disease, such as asbestos, strong inorganic acids, cement dust and free crystalline silica. Additionally, salted meat and total fat intake have been linked to elevated risk of laryngeal cancer. Conversely, several studies have confirmed that fruits, raw leaf vegetables and legumes protect against this cancer. Some researchers have postulated a possible association between laryngeal squamous cell carcinoma and human papilloma virus (HPV), but this is not universally accepted. Gastroesophageal reflux disease is weakly, but consistently correlated with laryngeal cancer. Familial cancer clusters, particularly of head and neck tumors, seem to increase the risk of laryngeal cancer. Some genetic polymorphisms, such as of genes that code for xenobiotic-metabolizing enzymes, have shown elevated risk for laryngeal cancer according to recent studies. Public health policies regarding the control of tobacco smoking and alcohol consumption, and also surveillance of carcinogen exposure in occupational settings, could have an impact on laryngeal cancer. No proposals for screening have been recommended for laryngeal cancer, but one diagnostic goal should be to avoid treatment delay when suspected symptoms have been observed.